Kinetics of magnetizing field of gravitational-magnetic concentrate in the presence of liquid hydrocarbon - Kochegina, Ye.V.; Khalikova, Z.S.; Absat, Z.B.; Karimova, A.B.; Rakhimzhanova, N.Zh.; Tusipkhan, A. (Изд-во КарГУ, 2013)
Calculation of activation energy and kinetic parameters of magnetization combustion of Lisakovsk gravitational-magnetic concentrate in the presence of liquid hydrocarbons (oils of different deposits) was made. The conditions of thermo-gravitational processing were chosen. It was established that catalytic destruction of or- ganic compounds of liquid hydrocarbons adsorbed on oolits allowed decreasing temperature of dehydration and reduction of gravitational-magnetic concentrate.
Keywords: kinetics; liquid hydrocarbon; Lisakovsk ironstone gravity-magnetic concentrate; hydrocarbon feedstock; effective additive